The specific problems of the recovery of Historical architectural monuments of Kashkadarya region (Journal of Universal Science Research, 2023)
In the article shows that It was found that there were several problems in the field of urban development practices aimed at preserving historical-architectural objects in the region in the first years of independence, that the master plans of the historical centers of ancient cities were not up to the required level, which caused distortions in their compositional-architectural appearance, and that the practice of eliminating these mistakes in the first years of independence was also not perfect, it is stated that practical works are being carried out in this field today.